A review on the valorisation of food waste as a nutrient source and soil amendment. (1st March 2021) - O'Connor, James; Hoang, Son A.; Bradney, Lauren; Dutta, Shanta; Xiong, Xinni; Tsang, Daniel C.W.; Ramadass, Kavitha; Vinu, Ajayan; Kirkham, M.B.; Bolan, Nanthi S.
Abstract: Valorisation of food waste offers an economical and environmental opportunity, which can reduce the problems of its conventional disposal. Food waste is commonly disposed of in landfills or incinerated, causing many environmental, social, and economic issues. Large amounts of food waste are produced in the food supply chain of agriculture: production, post-harvest, distribution (transport), processing, and consumption. Food waste can be valorised into a range of products, including biofertilisers, bioplastics, biofuels, chemicals, and nutraceuticals. Conversion of food waste into these products can reduce the demand of fossil-derived products, which have historically contributed to large amounts of pollution. The variety of food chain suppliers offers a wide range of feedstocks that can be physically, chemically, or biologically altered to form an array of biofertilisers and soil amendments. Composting and anaerobic digestion are the main large-scale conversion methods used today to valorise food waste products to biofertilisers and soil amendments. However, emerging conversion methods such as dehydration, biochar production, and chemical hydrolysis have promising characteristics, which can be utilised in agriculture as well as for soil remediation. Valorising food waste into biofertilisers and soil amendments has great potential to combat land degradation in agricultural areas. Biofertilisers are rich in nutrients that can reduce the dependability of using conventional mineral fertilisers. Food waste products, unlike mineral fertilisers, can also be used as soil amendments to improve productivity. These characteristics of food wastes assist in the remediation of contaminated soils. This paper reviews the volume of food waste within the food chain and types of food waste feedstocks that can be valorised into various products, including the conversion methods. Unintended consequences of the utilisation of food waste as biofertilisers and soil-amendment products resulting from their relatively low concentrations of trace element nutrients and presence of potentially toxic elements are also evaluated. Graphical abstract: Image 1 Highlights: Food wastes are produced during food production, processing and consumption stages. Valorisation technologies of food wastes include composting, dehydration, anaerobic digestion and pyrolysis. The supply of carbon and nutrients to soil by food waste products is dependent on the valorisation technologies. Food waste valorisation products improve soil health and crop productivity. The unintended impacts of food waste valorisation products include soil salinity and contamination.